Efficacy and safety of Qingre-Chushi therapies in active ulcerative colitis: A network meta-analysis. - Ling Zhang (Public Library of Science (PLoS), 2021)
Background Ulcerative colitis (UC) is a chronic inflammatory disease with an increasing incidence in the world. Qingre-Chushi therapies (QC) can alleviate clinical symptoms. Therefore, a network meta-analysis was conducted to systematically evaluate the efficacy and safety of QC in the treatment of active UC patients. Methods 7 databases were screened and relevant randomized controlled trials were selected. The tools of Cochrane Handbook and the GRADE system were conducted to assess the quality of outcomes. Pooled risk ratio or standard mean difference was calculated with 95% credible interval for outcomes measurement using the random-effects model. The surface under the cumulative ranking curve (SUCRA) was performed to rank the treatments. The larger SUCRA scores, the more effective interventions. Results A total of 3560 articles were identified and 21 studies including 1829 participants were included for further analysis. Totally, 9 therapies regimens were compared: oral mesalazine, mesalazine enema, mesalazine suppository, oral mesalazine + mesalazine enema, oral QC, oral QC + oral mesalazine, QC enema, oral QC + QC enema, and oral mesalazine + QC enema. Based on the SUCRA plot, oral QC + oral mesalazine was the best treatment in inducing clinical response; oral QC + QC enema had the best efficacy in the improvement of Mayo scores and alleviating abdominal pain; oral mesalazine + mesalazine enema was the optimal therapy in the endoscopic improvement and reducing diarrhea; QC enema + oral mesalazine was the best option in preventing bloody stool. Conclusion This study confirmed the efficacy and safety of QC in treating active UC and suggested that the combination of oral medications with topical can achieve more benefits.